Biomimicry in relation with islamic value - Mohd Rosdi, Aini Atiqah; Abd Rahman, Khairul Aidil Azlin (Universiti Pendidikan Sultan Idris, 2019)
This paper explore the relationship between biomimicry and Islamic value especially in the context of ecosystem. Human activity directly and indirectly is, our conscious action to refine our environment. The method used in this paper is Kawakita Jiro method and various literature review to achieve the conceptual framework for further research investigation. Humankind value was brought to the attention as the crucial part to preserve the environment thus the utilization of biomimicry can assist better comprehension in humanity. Therefore, this study aims to perceive the correlation of the human’s belief is part of the value to develop a healthy environment. This include biomimicry as one source of inspiration used in nature. It helps the human to enhance well-being by connecting to the nature or the element which remind us of nature.